2019
DOI: 10.1371/journal.ppat.1007852
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of transcription initiation across latent and lytic KSHV genomes

Abstract: Precise promoter annotation is required for understanding the mechanistic basis of transcription initiation. In the context of complex genomes, such as herpesviruses where there is extensive genic overlap, identification of transcription start sites (TSSs) is particularly problematic and cannot be comprehensively accessed by standard RNA sequencing approaches. Kaposi's sarcoma-associated herpesvirus (KSHV) is an oncogenic gammaherpesvirus and the etiological agent of Kaposi’s sarcoma and the B cell lymphoma pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 78 publications
1
26
0
Order By: Relevance
“…The cell type specific expression of vIRF3 and vIL-6 suggests that KSHV might have different latency programs depending on the type of infected cell. In fact this has been observed in a recent study [79] comparing latency in TREx-BCBL1RTA and iSLK.219. Another type of exception to the canonical latency program of the four major latency proteins is the K1 protein, which is expressed in latency at low levels and is induced in the lytic cycle [72,80].…”
Section: Viral Gene Expression Patterns In Latencymentioning
confidence: 60%
“…The cell type specific expression of vIRF3 and vIL-6 suggests that KSHV might have different latency programs depending on the type of infected cell. In fact this has been observed in a recent study [79] comparing latency in TREx-BCBL1RTA and iSLK.219. Another type of exception to the canonical latency program of the four major latency proteins is the K1 protein, which is expressed in latency at low levels and is induced in the lytic cycle [72,80].…”
Section: Viral Gene Expression Patterns In Latencymentioning
confidence: 60%
“…Widespread pre-mRNA splicing within the KSHV transcriptome. We recently reported a transcriptome-wide single-nucleotide resolution map of KSHV transcription start sites (TSSs) using RNA annotation and mapping of promoters for analysis of gene expression (RAMPAGE) 28 . In our analyses, we unexpectedly observed several unannotated introns, including many positioned downstream of a termination codon, rendering the transcripts potential NMD substrates.…”
Section: Resultsmentioning
confidence: 99%
“…While only 27 introns were previously described, our study identified 372 and 68 introns within iSLK.219 and TREx-BCBL1-RTA cells, respectively 31 . These analyses coupled with recent efforts to map the TSS landscape of KSHV underscores that we still lack a complete annotation of the KSHV transcriptome, and that viral transcript architecture is cell-type specific 28 .…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we chose to silence LANA, a key mediator of latent viral replication that tethers the viral episome to host chromosomes by bridging the interaction between the KSHV genome and host chromatin [ 40 , 41 , 42 ]. To test whether CRISPRi repressed LANA, we transduced iSLK-219-dC9K cells with sgRNAs targeting the LTc promoter ( Table S2 , Figure 3 A), which is known to be preferentially used for LANA transcription in these cells [ 6 ]. Two weeks after transduction, we selected the upper quartile of BFP + /sgRNA + expressing cells by FACS and evaluated LANA levels in this population.…”
Section: Resultsmentioning
confidence: 99%
“…KSHV has a large, circular dsDNA genome of 160–170 Kb, which encodes over 90 open reading frames (ORFs), more than two dozen short ORFs and upstream ORFs, circular RNAs, several long noncoding RNAs (ncRNAs), and 25 micro RNAs [ 5 , 6 ]. Functional genomics studies have revealed the role of several viral ORFs and ncRNAs in immunomodulation [ 7 ], oncogenesis [ 3 , 8 ], and the basic biology of the abduction of the cellular machinery by the virus [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%